The (World Wide) Work 2.0: The Gurdjieff Tradition Online. (20th September 2016) - Cusack, Carole; Pecotic, David
Abstract : The occult and the internet intersect in four ways: as a static medium for information; as a space where contested information or ideological conflict may occur; as a facilitator of communication; and as a medium for esoteric practice. The last type of activity is rare, but it is intriguing, in that technology can shape and inform beliefs and practices in unanticipated ways. Online engagement with the 'Work', the movement produced by the Greek Armenian spiritual teacher and esotericist G. I. Gurdjieff (c. 1866-1949) and his immediate followers, is an under-researched instance of online esoteric practice. This article addresses this scholarly desideratum, bringing the theoretical approaches of online religion and digital ethnography to bear on the Gurdjieff Internet Guide (GIG) website, founded by Reijo Oksanen (b. 1942) and later maintained by Kristina Turner, who created an accompanying Facebook page. The GIG manifests a shift away from the sectarian secrecy of the 'Foundation' groups, founded by Jeanne de Salzmann (1889-1990) after Gurdjieff's death to formalise and protect the content of the Work, and the limited web presence that the Foundation permits. The GIG moves towards an ecumenical 'open source' approach to the dissemination of Gurdjieff's teachings rooted in independent groups founded by other first generation followers of Gurdjieff who remained outside of the Foundation. It is argued that the deregulation of the religious and spiritual marketplace of the contemporary West, coupled with the dominant role played by the Internet in disseminating information, has radically transformed the Gurdjieff tradition, collapsing hierarchies and esoteric strategies, democratizing access for seekers, and creating new ritual and teaching modes.